In utero transfer of adeno-associated viral vectors produces long-term factor IX levels in a cynomolgus macaque model - Mattar, Citra Nurfarah Zaini; Gil-Fariña, Irene; Käppel, Christine; Schmidt, Manfred (Molecular therapy, 2017)
The safe correction of an inherited bleeding disorder in utero prior to the onset of organ damage is highly desirable. Here, we report long-term transgene expression over more than 6 years without toxicity following a single intrauterine gene transfer (IUGT) at 0.9G using recombinant adeno-associated vector (AAV)-human factor IX (hFIX) in the non-human primate model we have previously described. Four of six treated animals monitored for around 74 months expressed hFIX at therapeutic levels (3.9%-120.0%). Long-term expression was 6-fold higher in males and with AAV8 compared to AAV5, mediated almost completely at this stage by random genome-wide hepatic proviral integrations, with no evidence of hotspots. Post-natal AAV challenge without immunosuppression was evaluated in two animals exhibiting chronic low transgene expression. The brief neutralizing immune reaction elicited had no adverse effect and, although expression was not improved at the dose administered, no clinical toxicity was observed. This long-term surveillance thus confirms the safety of late-gestation AAV-hFIX transfer and demonstrates that postnatal re-administration can be performed without immunosuppression, although it requires dose optimization for the desired expression. Nevertheless, eventual vector genotoxicity and the possibility of germline transmission will require lifelong monitoring and further evaluation of the reproductive function of treated animals.